Regional Government Authority in the Implementation of Natural Disaster Management - Suwari Akhmaddhian; Teten Tendiyanto; Roni Nursyamsu; Alif Faisal Abdilah; Azmy Sabila Gustianitami (Universitas Kuningan, 2022)
Natural disasters certainly have negative impact on the environment and society in community health, comfort, and economic conditions. This study aims to asertain and analyze the regulation─regional government service authority in organizing natural disaster management in Indonesia. This study employed empirical legal method involving primary and secondary data and was conducted in Kuningan Regency. The data were collected through interviews, observations and literature studies. The finding revealed the regional government service authority is governed in Article 9 of Law Number 24 of 2007─Disaster Management, Government Regulation of the Republic of Indonesia Number 21 of 2008─the Implementation of Disaster Management, and Regional Regulation Number 6 of 2011─ the Implementation of Disaster Management. Finally, their authority is mostly defined clearly in Law Number 24 of 2007 concerning Disaster Management. This law establishes apparent rules that each duty and function is already appropriate.